Role of Omentin, Vaspin, Cardiotrophin-1, TWEAK and NOV/CCN3 in Obesity and Diabetes Development - Escoté, Xavier; Gómez-Zorita, Saioa; López-Yoldi, Miguel; Milton-Laskibar, Iñaki; Fernández-Quintela, Alfredo; Martínez, J.; Moreno-Aliaga, María; Portillo, María (International journal of molecular sciences, 2017)
Adipose tissue releases bioactive mediators called adipokines. This review focuses on the effects of omentin, vaspin, cardiotrophin-1, Tumor necrosis factor-like Weak Inducer of Apoptosis (TWEAK) and nephroblastoma overexpressed (NOV/CCN3) on obesity and diabetes. Omentin is produced by the stromal-vascular fraction of visceral adipose tissue. Obesity reduces omentin serum concentrations and adipose tissue secretion in adults and adolescents. This adipokine regulates insulin sensitivity, but its clinical relevance has to be confirmed. Vaspin is produced by visceral and subcutaneous adipose tissues. Vaspin levels are higher in obese subjects, as well as in subjects showing insulin resistance or type 2 diabetes. Cardiotrophin-1 is an adipokine with a similar structure as cytokines from interleukin-6 family. There is some controversy regarding the regulation of cardiotrophin-1 levels in obese -subjects, but gene expression levels of cardiotrophin-1 are down-regulated in white adipose tissue from diet-induced obese mice. It also shows anti-obesity and hypoglycemic properties. TWEAK is a potential regulator of the low-grade chronic inflammation characteristic of obesity. TWEAK levels seem not to be directly related to adiposity, and metabolic factors play a critical role in its regulation. Finally, a strong correlation has been found between plasma NOV/CCN3 concentration and fat mass. This adipokine improves insulin actions.